Predictors of Time to Completion of Graduate Degrees - Sheridan, Peter M.; Pyke, Sandra W. (Canadian Journal of Higher Education, 1994)
A multiple regression procedure was utilized to predict the time taken to complete graduate degree requirements for 395 master’s and 79 doctoral students at a large Canadian university. Selected demographic (e.g., sex, age, marital status, registration status, citizenship), academic (e.g., undergraduate and graduate GPA, discipline, type of program) and financial support variables (funding received from internal and external scholarships and from research, graduate and teaching assistantships) were used as independent variables. Results for master’s students indicate that full-time registration, increased financial support, higher graduate GPA and enrolment in a humanities discipline significantly decrease time to completion. Conversely, a thesis requirement and Canadian citizenship are associated with significantly slower degree progress. For doctoral students, enrolment in a natural sciences discipline, Canadian citizenship, full-time registration and increased funding significantly decrease the time taken to complete the doctorate.